2010
DOI: 10.1109/tnet.2010.2053381
|View full text |Cite
|
Sign up to set email alerts
|

Near-Optimal Multicriteria Spanner Constructions in Wireless Ad Hoc Networks

Abstract: Abstract-In this paper we study asymmetric power assignments which induce a low energy k-strongly connected communication graph with spanner properties. We address two spanner models: energy and distance. The former serves as an indicator for the energy consumed in a message propagation between two nodes, while the latter reflects the geographic properties of routing in the induced communication graph. We consider a random wireless ad-hoc network with |V | = n nodes distributed uniformly and independently in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Additional applications of such spanners in distributed systems include network synchronization and computing global functions [Awe85, PU89a, ABP90, ABP91, Pel00]. Light and sparse spanners were also found useful for various data gathering and dissemination tasks in overlay networks [BKR + 02, VWF + 03, KV02], in wireless and sensor networks [vRW04, BSDS04,SS10], for VLSI circuit design [CKR + 91, CKR + 92a, CKR + 92b, SCRS01], for routing [WCT02,PU89a,PU89b,TZ01b], to compute distance oracles and labels [Pel99,TZ01a,RTZ05], and to compute almost shortest paths [Coh93, RZ04, Elk05, EZ06, FKM + 05]. Low degree spanners are also very useful in many of these applications.…”
mentioning
confidence: 99%
“…Additional applications of such spanners in distributed systems include network synchronization and computing global functions [Awe85, PU89a, ABP90, ABP91, Pel00]. Light and sparse spanners were also found useful for various data gathering and dissemination tasks in overlay networks [BKR + 02, VWF + 03, KV02], in wireless and sensor networks [vRW04, BSDS04,SS10], for VLSI circuit design [CKR + 91, CKR + 92a, CKR + 92b, SCRS01], for routing [WCT02,PU89a,PU89b,TZ01b], to compute distance oracles and labels [Pel99,TZ01a,RTZ05], and to compute almost shortest paths [Coh93, RZ04, Elk05, EZ06, FKM + 05]. Low degree spanners are also very useful in many of these applications.…”
mentioning
confidence: 99%
“…One of the most popular applications of the spanners is to serve as overlay networks in wireless networks [vRW04,BDS04,SS10]. In these applications, we are often interested in solving computational problems in the spanner, such as shortest path [LWF03,GZ05], independent set [Bas01,MM09], dominating sets [MM09,PCAT18], connected dominating set [YWWY13].…”
Section: Algorithmic Implicationsmentioning
confidence: 99%
“…Over more than 30 years, research on spanners has evolved into an independent field of study, and has found numerous applications, such as to VLSI circuit design [CKR + 91, CKR + 92, SCRS01], to distributed computing [Awe85, ABP92, Pel00], to approximation algorithms [RS98, Kle05, Kle06, Got15, BLW17, CFKL20], to wireless and sensor networks [vRW04,BDS04,SS10], to machine learning [GKK17], and to computational biology [RG05]. Spanners enjoy wide applicability since they possess many desirable properties such as low sparsity, implying, e.g., low storage cost; small lightness, implying, e.g., low construction cost; low maximum degree, implying, e.g., small routing tables in routing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Various spanner constructions have been analyzed on uniformly distributed point sets [1,8,13,25,27]. Some of these constructions are a t-spanner for fixed t, others are parameterizable with arbitrary t > 1.…”
Section: Introductionmentioning
confidence: 99%